2021
DOI: 10.1002/aur.2620
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine ameliorates valproicacid‐inducedhyperactivity, anxiety‐like behavior, and social interaction deficits in zebrafish

Abstract: Syndromic autism spectrum disorders (ASDs) are characterized by impaired social communication and repetitive/stereotyped behaviors. Currently available therapeutic agents against ASD have limited efficacy. Thus, searching for novel and effective drugs ameliorating core symptoms, in particular social deficits, is of utmost importance. Duloxetine (DLX), an antidepressant that has been identified as an agonist mimetic for the cell adhesion molecule L1, exhibits beneficial functions in vitro and in vivo. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 78 publications
7
16
0
2
Order By: Relevance
“…Percentage of mortality profoundly increased across concentrations, denoting contradictory outcomes with the study by Chen et al (2018), which reported zero embryonic mortality for all tested concentrations (0, 5, 50, 500, 1000, and 1500 μM). However, the parallel trend concluded by Joseph et al (2022) and Dwivedi et al (2019) supported the data of this study. Additionally, VPA levels started to decrease following 48 h of treatment, suggesting that it was absorbed by the embryos (Zimmermann et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Percentage of mortality profoundly increased across concentrations, denoting contradictory outcomes with the study by Chen et al (2018), which reported zero embryonic mortality for all tested concentrations (0, 5, 50, 500, 1000, and 1500 μM). However, the parallel trend concluded by Joseph et al (2022) and Dwivedi et al (2019) supported the data of this study. Additionally, VPA levels started to decrease following 48 h of treatment, suggesting that it was absorbed by the embryos (Zimmermann et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, when applied in spinal cord injury models as a recombinant glycoprotein or when overexpressed by adeno-associated virus in stem cell-derived neural Biomolecules 2022, 12, 439 2 of 16 aggregates, Schwann cells and radial glial cells, L1 accelerated remyelination and improved axonal regrowth/sprouting/sparing proximal, distal and across the lesion site [9][10][11][12]. In addition, L1 ameliorated the severe consequences of injury in experimental models of neurodegenerative diseases in vitro and in vivo [13][14][15][16][17]. Since the viral delivery of L1, application of recombinant L1, and injection of stem cells overexpressing L1 are expected to meet difficulties in translation to therapy, libraries of small organic molecules were screened for compounds that structurally and functionally mimic L1, and several molecules were found to act as L1 agonistic mimetics [18].…”
Section: Introductionmentioning
confidence: 99%
“…There were no statistical differences in the average swimming speed among all treatment groups. Behaviors such as social interactions might have higher sensitivity to the effects of anxiolytics and antidepressants than the usual metric of swimming speed of fish (Bencan et al, 2009; Joseph et al, 2022; Takai et al, 2022). Hence we suggest that the response to an image of a predator fish can be a suitable parameter for assessing the effect of anxiolytics on fish behavior.…”
Section: Resultsmentioning
confidence: 99%